Pennsylvania literary journal (Indiana, Pa. : Anna Faktorovich, 2009)
Includes critical essays, book-reviews and poetry ... created to make a positive contribution to literary criticism and literature around the world.
Description based on: Summer 2009; title from website (viewed Oct. 9, 2009).
Latest issue consulted: Summer 2010.
Keywords: 2000-2099; English literature -- History and criticism -- Periodicals; English literature -- 21st century -- Periodicals; English literature; Literature - General; Electronic journals